Supporting residential energy conservation under constrained public budget: Cost-effectiveness and redistribution analysis of public financial schemes in France - Bettina Chlond; Claire Gavard; Lisa Jeuck (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
In the context of tight public budgets and increasingly ambitious climate objectives, the performance of the support policies for residential energy conservation works needs to be assessed. We compare the performance of four types of support schemes in France, namely the income tax credit, a grant scheme, the reduction of the value-added tax, and the White Certificates scheme. The analysis employs a dataset covering close to 14,000 French households who conducted conservation works in France. To address self-selection bias and potential endogeneity concerns, we use a double-robust inverse probability weighting estimator, a method mostly used in epidemiology so far. We assess the effect of the adoption of each scheme on the funding acquired, the private investment, total investment and the reduction of the household energy expenses. We deduct metrics of cost-effectiveness, redistribution and the ability to trigger private investment and additional total investment in energy conservation works via the schemes. We find funding from the schemes to reduce energy expenses most cost-effectively via the White Certificates. Additional private and total investment is highest with the adoption of the VAT reduction. The redistribution of public funds to low-income households is highest with the grant scheme.
Keywords: H23; Q58; Q48; 330; Energy efficiency; energy conservation; residential retrofits; cost-effectiveness; re-distribution; inverse probability weighting